Birds’ species diversity measurement of Uchali Wetland (Ramsar site) Pakistan - Taofik, Oyedele Dauda; Baksh, Md. Hafiz; Mohd. Sah Shahrul, Anuar (Elsevier, 2017)
We carried out this study to evaluate bird species diversity and to model bird species abundance using Uchali Wetland, Pakistan (32330N, 72010E). Data obtained were subjected to summary statistics, Simpson diversity, Shannon evenness index, and rank abundance curve and model. The watershed supports 25,361 birds of 47 species, which is appreciably less than the number of bird species supported by the same wetland in the past year (1991). Total evenness could be obtained as the ranks increases and this differed annually. Evenness index (EI) analysis showed that EI for 2011 was 0.0231, for 2012, it was 0.02, for 2013, it was 0.01, and for the annual mean, it was 0.046 indicating functional abundance of the species. Bird species diversity measurement could be enhanced by the use of the modified rank eabundance curve and would clearly present the true picture of the bird species abundance.